2011
DOI: 10.1111/j.1365-2966.2011.20011.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase lags of solar hemispheric cycles

Abstract: The North-South asymmetry of solar activity is variable in time and strength. We analyse the long-term variation of the phase lags of hemispheric cycles and check a conjectured relationship between these phase lags and the hemispheric cycle strengths. Sunspot data are used from cycles 12-23 in which the separation of northern and southern hemispheres is possible. The centers of mass of the hemispheric cycle profiles were used to study the phase relations and relative strengths of the hemispheric cycles. This a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Sunspots and other forms of solar magnetic activity are not uniformly distributed in solar longitude, but are centered around certain longitude bands, which are called active longitudes (ALs). Active longitudes have been observed in several studies using different data bases (Temmer et al 2006;Chen et al 2011;Li 2011;Muraközy & Ludmány 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Sunspots and other forms of solar magnetic activity are not uniformly distributed in solar longitude, but are centered around certain longitude bands, which are called active longitudes (ALs). Active longitudes have been observed in several studies using different data bases (Temmer et al 2006;Chen et al 2011;Li 2011;Muraközy & Ludmány 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It also shows that there can be a dominant hemisphere for the duration of a full cycle and that sequences of several cycles can exhibit the same hemispheric bias. It should be mentioned here that although a relationship between hemispheric asymmetry and cycle maximum SSN has not been established, it has been suggested that there is a longer‐term periodicity in the preferred hemisphere, possibly associated with the proposed grand cycle (e.g., Murakozy & Ludmany, ; Schussler & Cameron, ). (If their pattern persists, Cycle 25 will have dominant northward activity.)…”
Section: A Dynamo Master Clock?mentioning
confidence: 91%
“…There are more sunspots in NH for 1950-1970 and excess sunspots in SH for descent of cycles 21-23 (1980-2010) more so for the Cycle 24 decay phase (Svalgaard and Kamide, 2013; Ahluwalia, 2015bAhluwalia, , 2016. Murakozy and Ludm´any (2012) analyzed hemispheric SSN data from the Greenwich Royal Observatory for 12 cycles (12-23), finding phase of hemispheric cycles shows an alternating variation; NH leads in 4 and follows in 4 cycles, 4+4 cycle period is close to Gleissberg (1939) cycle; Zolotova et al (2009) reached a similar conclusion. Vernova et al (2014) find that the Cycle 24 may be violating this rule.…”
Section: Ssn(v2)mentioning
confidence: 99%